Establishment of Core Collection of Sweetpotato (Ipomoea Batatas L.) Germplasm Using RAPD Markers - Harouna, Sow (2006)
Sweetpotato (Ipomoea batatas LAM.) is among the world’s most important, versatile and underexploited food crop after rice, wheat, maize and cassava based on fresh-weight basis in developing countries. The presence of high level of genetic diversity in germplasm of sweetpotato is reflected in the big number of accessions being maintained at various genebanks around the world. Maintenance of these germplasm collections can be a problematic and costly activity. Germplasm rationalization can facilitate maintenance and utilization of the available germplasm. Identification of core collection is one of the essential steps in rationalization. Core collection normally established based on qualitative and quantitative characteristics of morphological data. Morphological markers, however, have some disadvantages because they are often subjected or converged according to development and environmental variation / changes. Establishment of a core collection based on genetic variation using molecular markers can be advantageous due to the absence of environmental and developmental stage variation. The main objectives of this study were to use RAPD markers to investigate the genetic diversity of sweetpotato germplasm, and consequently to establish a core collection based on the RAPD polymorphism.